Biofortification: A food-systems solution to help end hidden hunger - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Available online. Part of an ongoing collaboration, which has also involved the World Health Organization (WHO). WHO and FAO convened a 2016 technical consultation to review scientific evidence and other technical aspects of biofortification. A 2017 special issue was published with inputs from HarvestPlus and other CGIAR researchers.